2019
DOI: 10.1259/bjr.20180389
|View full text |Cite
|
Sign up to set email alerts
|

Current and future applications of 3D printing in congenital cardiology and cardiac surgery

Abstract: et al. Current and future applications of 3D printing in congenital cardiology and cardiac surgery. Br J Radiol 2018; 91: 20180389.aBStract Three-dimensional (3D) printing technology in congenital cardiology and cardiac surgery has experienced a rapid development over the last decade. In presence of complex cardiac and extra-cardiac anatomies, the creation of a physical, patient-specific model is attractive to most clinicians. However, at the present time, there is still a lack of strong scientific evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
0
32
0
3
Order By: Relevance
“…Another noteworthy observation was that none of the papers we found discussed 3DP in critical care for adult cardiac disease. Although 3DP in cardiac medicine is a well-established field of research with various reviews [8,47], 3DP utilization in adult cases mainly revolve around defect visualization, procedural planning, and surgical device innovation [47]. The scarcity of medical education utilities in adult cardiology is represented by both our results and those reported by Vukicevic and colleagues in their review of 3DP uses in cardiac medicine [47].…”
Section: Results Interpretationmentioning
confidence: 57%
See 1 more Smart Citation
“…Another noteworthy observation was that none of the papers we found discussed 3DP in critical care for adult cardiac disease. Although 3DP in cardiac medicine is a well-established field of research with various reviews [8,47], 3DP utilization in adult cases mainly revolve around defect visualization, procedural planning, and surgical device innovation [47]. The scarcity of medical education utilities in adult cardiology is represented by both our results and those reported by Vukicevic and colleagues in their review of 3DP uses in cardiac medicine [47].…”
Section: Results Interpretationmentioning
confidence: 57%
“…Over the past few decades, many medical subspecialties began using 3DP for a variety of purposes. For example, cardiac surgeons began using computed tomography scans to create 3DP models of patients' hearts to help with surgical planning [8]. This widespread use of 3DP in medicine has become prevalent enough to create special interest groups to devise appropriateness criteria of 3DP utilization in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective, multicenter study demonstrated that 3DP models led to change in the surgical strategy in 19 of 40 cases. 4,5 Moreover, combining 3DP technology with the use of virtual surgery can potentially allow physical examination of the spatial relationship of an intracardiac baffle or device in relation to the valves, ventricles, and surrounding structures. In addition to their clinical applications, these models unquestionably have a great educational value to explain the morphology of complicated congenital defects, to facilitate communication with the families, and, finally, to teach congenital cardiac surgery to trainees.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 99%
“…Three-dimensional (3D)-printing technology has become a popular field of biomedical study in recent years; this is a rapid prototyping technology based on digital model files and is used to print a solid object form with complex geometry through layered processing. [13][14][15] In 2012, Scottish scientists used 3D-printing technology to print artificial liver tissue using human cells, which established the basis for the application of 3D-printing technology in the medical field. In recent years, continuous improvements in technology have increased the use of 3D printing in accordance with the characteristics of individualized and precision medicine, and 3D-printing technology has been widely applied in clinical medicine.…”
Section: Introductionmentioning
confidence: 99%